An open source and reduce expenditure ROS generation strategy for chemodynamic/photodynamic synergistic therapy - Conghui Liu (Nature Portfolio, 2020)
The supply of oxygen species for dynamic therapy is a major limitation. Here, the authors report on a complex of calcium peroxide with photo/chemo dynamic agents, where NIR heating causes the release of calcium peroxide to generate oxygen and hydrogen peroxide for photodynamic and chemodynamic therapy.